Tablet Formulation Containing Chitosan-Alginate Microparticles: Characterization and Release Profile of Xanthones - Elsa Anisa Krisanti; David Lazuardi; Kianti Kasya Kiresya; Kamarza Mulia (International Journal of Technology, 2020)
Mangosteen pericarp extract contains a high amount of xanthones, which are secondary plant metabolites that exhibit high antioxidant activities as well as beneficial pharmacological properties, but low bioavailabilities. In this study, xanthones extracted from the pericarp of soursop fruit were encapsulated in chitosan-alginate microparticles by ionic gelation, and the microparticles were subsequently formulated into antioxidant supplement tablets by direct compression. One of the tablet formulations satisfied the requirements for weight and size uniformity as well as friability, but not hardness. Dissolution test results revealed similar release profiles characterized by a burst release that occurs in the first 60 min of immersion in simulated gastrointestinal fluids and a complete release of xanthones in 120 min. The results obtained herein demonstrated the potential of the tested tablet formulations for the delivery of xanthones into the gastrointestinal tract. If a targeted release to a specific area in the gastrointestinal tract is desirable, the composition of the excipients in the present formulation should be modified.